Between disability and translation. Persons with disabilities as creators and recipients of translations - Figiel, Wojciech (Understanding Disability: Issues, Research, Reflections, 2021)
This paper deals with the relations between the phenomena of disability and translation studies. Translation studies and disability studies are relatively new fields, which up until recently had little in common. However, for more than a dozen years now, scholars of translation have focused on research concerning access services for people with disabilities. These services include, among others, audio description, sign language interpretation and subtitles for the deaf and the hard of hearing. However, there is not too much research concerning people with disabilities as creators, and not recipients, of translation. There is also a lack of translation scholars with disabilities. The interdisciplinary perspective of sociology of translation and disability studies may help to bridge this gap by providing a more inclusive approach to studies on translation.